Contrasting the Performance of Active and Passive Unit Trusts under Normal Market Conditions: Is the Experience of Emerging Markets Different? - Gopane, Thabo J.; Ravhura, Mukundi (Organizations and Markets in Emerging Economies, 2024)
The predominant tradition in the literature is to scrutinise the competitive performance of passive and active investment strategies with less regard to the prevailing market climate. The thesis of this paper is that volatile market conditions may necessitate investment strategy adjustments. Such readjustments may confound empirical comparison of passive and active investing if econometric models do not adapt accordingly. Currently, the literature cannot give a stylised fact of whether the historical claims of passive–active relationships relate to normal market conditions or not, which is a flaw. The present study reduces the flagged knowledge gap by answering the question whether passive investment outperforms active investing under normal market conditions. The study applies the parametric and non-parametric risk-adjusted models of the Jensen alpha and Sharpe index. The empirical analysis is based on the weekly returns of 16 unit trusts listed on South Africa’s Johannesburg Stock Exchange for ten years (between 2009 and 2019). Consistent with the hypothesis of inefficient capital markets in developing economies, the study finds that active investing significantly outperforms passive investment strategy under normal market conditions. The results should benefit investors and policymakers in the era of increasing competitiveness, digitalisation, and globalisation.